CONGENITAL INTERNAL HYDROCEPHALUS IN A FOAL - GUPTA, M; SHARMA, N; KISHORE, N (The Indian Journal of Animal Reproduction, 2023)
A rare case of successful delivery of a Hydrocephalic Foal was recorded.